Translation Quality of Arabic Directive Speech Acts in Pandemic’s Book: An Attempt to Delve into Covid-19 - Nurul Aini Choiriyah; M Yunus Anis; Syed Nurulakla bin Syed Abdullah; Nor Azuwan Yaakob (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
This study aimed to describe the types of directive speech acts, the use of translation techniques, and the quality of the Indonesian translation of the book Badzl al-Mâ'ûn fi Fadhl ath-Thâ'ûn. This research used descriptive analysis to describe the findings; the qualitative was chosen as the method of this study. Consequently, the data were analyzed using Miles and Huberman's and Spradley's models. The results of this study stated that there were 60 data consisting of eight directive speech act types, where the frequency of using the technique was found 527 times for 15 techniques. Of the 60 data, 32 were translated accurately, acceptably, and with a high degree of readability and fell into the 'good' category. The average score for translation quality was 2.69. The study's contribution was to analyze Arabic texts translated into Indonesian using pragmatic models and measure their quality so that readers can quickly grasp the pandemic study from the perspective of the Arabic text.